Dietary exposure and health risk assessment of fumonisins through the consumption of maize and maize-based gluten-free products in individuals with celiac disease - Tuyben, Eylem Ezgi; Sevim, Sumeyra; Macit, Arife; Kizil, Mevlude (Frontiers in Nutrition, 2026)
IntroductionIndividuals with celiac disease (CD) must adhere to a gluten-free diet (GFD) and are therefore at high risk of fumonisin exposure due to their high consumption of maize and maize-based products. This study aimed to determine the concentrations of fumonisins (FB1, FB2, and FB3) in packaged gluten-free (GF) maize and maizebased products sold in Turkey and to assess dietary exposure and health risks in adults with CD using a probabilistic approach.MethodsFumonisin concentrations of 51 GF products were analyzed by Enzyme-Linked Immonosorbent Assay (ELISA) and daily food consumption data were collected from 67 individuals with CD through a food frequency questionnaire. Exposure was estimated using Estimated Daily Intake (EDI) values and probabilistic risk assessment with Monte Carlo simulation.ResultsThe highest fumonisins concentrations were detected in the pasta/rice/bulgur group, while the flour/starch group was the food group contributed most to total fumonisins exposure due to higher consumption. Although the average EDI values were below the Tolerable Daily Intake (TDI; 1 μg/kg bw/day) set by European Food Safety Authority’s (EFSA) and Provisional maximum tolerable daily intakes (PMTDI; 2 μg/kg bw/day) established by Joint Expert Committee on Food Additives’s (JECFA) values, individuals at the 95th percentile approached 132.88–167.89% of the PMTDI value in the flour/starch group and 79.00–82.38% in the pasta/rice/bulgur group.DiscussionThese findings highlight the need for continuous monitoring and stricter regulatory oversight and dietary guidance to protect vulnerable populations.